APLIKASI TEKNOLOGI TEPAT GUNA ALAT PEMARUT KELAPA PADA PROSES PRODUKSI VIRGIN COCONUT OIL (VCO) SKALA HOME INDUSTRY DI DESA BUMI WARAS, TELUK BETUNG SELATAN, BANDAR LAMPUNG - Utami, Herti (Jurnal Pengabdian Kepada Masyarakat Sakai Sambayan, 2019)
Coconut as a results farming is listed and abundant in the province Lampung, especially in Bandar Lampung. In Bandar Lampung, has vegetable sales community that stated in the Bumi Waras region, Teluk Betung Selatan County. One of the concerns of the vegetables sales community is a coconut results farmer. We take a vegetable sales community as a partner in this activity, because they have a lot of problems about coconut after sales. Coconut that not salable sold will be moldy and decaying in fast. There should be a way to overcome this problem by making a coconut likeness of the derivative products. The solution offered to overcome the problems is right to the application of technology to process the oil into products were chosen in terms of coconut by virgin coconut oil (vco) using the tools for the coconut cutting process easier and more efficient. In such a manner as there will be increasing the levels of value added of coconut into a product with higher derivatives of the having the benefit of and higher selling values. By this activity involved in marketing devotion is also arranging training on any process affecting the production the virgin coconut oil (vco) on the home industry scale. The selection of products VCO is because the easy to process and small capital, so will not burdensome to the public to go into business. With the assistance of the coconut cutting machine raising revenue among traders because the device is versatile and it could also be used to help the VCO production process. A method of the activities that would be used in their business over the devotion this is the method involving a partner or members of the population, especially a vegetable sales in their activities to get as a whole. The implementation of this activity in addition the results showed in the form of a cutting machine of the coconut from which equipped with a motor with a fuel and other equipment to press coconut to get coconut milk also needs to be undertaken a rise in their ability and knowledge partner or a member of community of a vegetable sales through training coconut product development in this case the practice of making VCO including the packaging commercially. The goals of this training were to the ability of making a product VCO can be to raise the income of in the programs as well.